Dual tolerance to soil drought and excess moisture stresses in cowpea genetic resources assessed using multiple indicators - Iseki, Kohtaro; Olaleye, Olajumoke (Frontiers in Plant Science, 2025)
IntroductionClimate change poses significant challenges to agriculture, particularly for upland crops in vulnerable regions. Cowpeas (Vigna unguiculata), a vital protein source in the dry savannah of West Africa, face production constraints due to yield variability from inconsistent rainfall patterns. Projections indicate an increase in extreme rainfall events, exacerbating excess moisture stress and complicating cultivation. This study evaluated the dual tolerance of cowpeas to both drought and excessive moisture by examining 99 genetic accessions, including both cultivated varieties and wild ancestors.MethodsA total of 99 cowpea accessions, comprising 54 cultivated accessions (Vigna unguiculata [L.] Walp.) and 45 wild ancestor accessions, were analyzed. Combinations of multiple indices with large genotypic variation—such as chlorophyll fluorescence, SPAD readings, and shoot biomass—were used to assess stress tolerance.ResultsWhile most accessions showed tolerance to only one stress or neither, ten accessions exhibited dual tolerance. Of the ten, nine were wild ancestors, underscoring the potential of wild genetic resources for crop improvement. As a factor underlying dual tolerance, we focused on the root morphological plasticity, allowing dynamic structural adjustments to different soil water conditions. Under excess moisture, a dual-tolerant accession formed lysigenous aerenchyma, facilitating oxygen diffusion and nitrogen fixation, while under drought conditions, it increased stele proportion. In contrast, a cultivar sensitive to both stressors exhibited lower plasticity, limiting its adaptability.ConclusionThis study highlights the importance of using multiple indices to assess stress tolerance, as different parameters reflect distinct physiological responses. The findings provide valuable insights for breeding climate-resilient cowpea varieties that can adapt to fluctuating soil water conditions.